2015
DOI: 10.1093/scipol/scv038
|View full text |Cite
|
Sign up to set email alerts
|

What determines researchers’ scientific impact? A case study of Quebec researchers

Abstract: Using a data set integrating information about researchers' funding and publication in the province of Quebec (Canada), this paper intends to identify the main determinants of citation counts as one measure of research impact. Using two-stage least square regressions to control for endogeneity, the results confirm the significant and positive relationship between the number of articles and citation counts. Our results also show that scientists with more articles in higher impact factor journals generally recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…It is not obvious that because women are less funded, they should receive fewer citations. For an equivalent amount of dollars raised in research funding, both men and women may exhibit similar citation rates, as they do in most disciplines with the exception of natural sciences (Mirnezami et al, 2015). Nevertheless, we suspect that women with a similar amount of funding will attract a smaller number of citations.…”
Section: H1mentioning
confidence: 88%
See 2 more Smart Citations
“…It is not obvious that because women are less funded, they should receive fewer citations. For an equivalent amount of dollars raised in research funding, both men and women may exhibit similar citation rates, as they do in most disciplines with the exception of natural sciences (Mirnezami et al, 2015). Nevertheless, we suspect that women with a similar amount of funding will attract a smaller number of citations.…”
Section: H1mentioning
confidence: 88%
“…A smaller proportion of women benefit from research funds (Stack, 2004), but both men and women receive an amount of grant proportional to the number of submittedproposals at NIH and NSF (Fox, 1991). Apart from many unpublished bibliometric research reports, little evidence exists as to the influence of research funding on the scientific impact of publications (two recent exceptions being Fortin and Currie, 2013;Mirnezami et al, 2015). For instance, Mirnezami et al (2015) showed that only in the natural sciences does funding have a positive and significant influence on the citation rate.…”
Section: H1mentioning
confidence: 99%
See 1 more Smart Citation
“…A past record of being funded by national agencies was identified as a common measurement of individual academic achievement (particularly productivity, quality and impact) in a number of papers and has been argued to be a reliable method that is consistent across medical research 111–113. For example, the National Institute of Health’s (NIH) Research Portfolio Online Reporting Tools system encourages public accountability for funding by providing online access to reports, data and NIH-funded research projects 111 114…”
Section: Resultsmentioning
confidence: 99%
“…Similar results have been reported by Robson and Mousquès ( 2016 ) for environmental modeling papers and by Wesel et al ( 2013 ) for several other disciplines. According to the case study by Mirnezami et al ( 2016 ) including researchers in Quebec (Canada), researchers who publish within larger teams of authors receive also more citation impact. There might be several reasons for the association between number of authors and number of citations: “We can think of a reference by n authors as having n times more proponents than a solo-authored one.…”
Section: Methodsmentioning
confidence: 99%